Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.9734/ijpss/2023/v35i244339
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Selected Plant Growth Regulators on Rooting Response of Stem Cuttings of Psidium guajava L.

Vanitha K.,
M. Kumar,
V. Sivakumar

Abstract: Guava can be propagated vegetatively through layering, cutting and grafting, in addition to seeds. Among the propagation techniques, cuttings have gained popularity because they produce results in a shorted span of time. Rooting is an essential step in the propagation of guava through cuttings. Nowadays, the most popular technique for growing cuttings in a misty environment is the use of plant growth regulators, especially auxins such as Indole-3-Butyric Acid (IBA) and Naphthalene Acetic Acid (NAA) that promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…However, in some species, the leaves are removed to reduce the loss of water due to transpiration (Sharma, 2012). Vanitha et al (2023) comparing cuttings namely single-node cutting with one leaf, double node cuttings with two leaves and herbaceous cuttings on rooting induction and found significant difference rooting success. While, Santoro et al (2010) studied the influence of leaf in the guava rooting and revealed that cutting with a pair of leaves had been superior to the parameters of the fresh and dry root mass while cutting without leaves showed no root formation.This result shows the essentiality of leaves presence for rooting.…”
Section: Influence Of Preparation Of Cuttingmentioning
confidence: 97%
See 3 more Smart Citations
“…However, in some species, the leaves are removed to reduce the loss of water due to transpiration (Sharma, 2012). Vanitha et al (2023) comparing cuttings namely single-node cutting with one leaf, double node cuttings with two leaves and herbaceous cuttings on rooting induction and found significant difference rooting success. While, Santoro et al (2010) studied the influence of leaf in the guava rooting and revealed that cutting with a pair of leaves had been superior to the parameters of the fresh and dry root mass while cutting without leaves showed no root formation.This result shows the essentiality of leaves presence for rooting.…”
Section: Influence Of Preparation Of Cuttingmentioning
confidence: 97%
“…In such circumstances, use of FYM and properly decomposed compost as growing media resolve the issue. Vanitha et al (2023) used growth media composed of sand, soil and well decomposed FYM in a 2:1:1 ratio for successful rooting induction.…”
Section: Influence Of Growing Media and Containermentioning
confidence: 99%
See 2 more Smart Citations
“…The formation of ARs is of great practical importance in horticulture, but many important plant species, especially those belonging to woody species, are difficult to root [9]. Since auxins have been shown to be effective in AR formation, exogenous application of auxin is used to promote rooting of cuttings in several plant species [10][11][12][13]. The most commonly used exogenous auxin is indole-3-butyric acid (IBA).…”
Section: Introductionmentioning
confidence: 99%